Induksi Kalus Binahong (Basella rubra L.) Secara In Vitro Pada Media Murashige & Skoog Dengan Konsentrasi Sukrosa Yang Berbeda - Sitorus, Ertina Novaria; Hastuti, Endah Dwi; Setiari, Nintya - (Bioma : Berkala Ilmiah Biologi, 2011)
Binahong (Basella rubra L.) is a plant medicine consisting secondary metabolites which have virtue asmedicines for several diseases that could also be used as coloring agent. The medicine compounds in secondarymetabolites could be extracted from callus. Sucrose is one of the components that build MS (Murashige & Skoog)medium. Sucrose is important in in vitro culture, it functions as carbon and energy source for explant to grow. Thepurposes of this research are to study the effect of sucrose in MS medium towards B. rubra L callus formation andgrowth; to find the optimum sucrose concentration for callus B. rubra L formation; and also to find the fastestinitiation time to produce callus crumb. This research uses Complete Random Design (CRD) single factor method,i.e., sucrose concentration of 0 g/l, 10g/l, 20 g/l, 30 g/l, 40 g/l with five repetitions. The data is analysed withAnalysis of Varian (Anova) and if a real difference is found the analysis is continued with Duncan Multiple RangeTest (DMRT) with significancy level of 95%. The results show that various sucrose concentrations in MS mediuminfluences callus B. rubra L induction. The highest sucrose concentration, i.e. 40 g/l, which was added into MSmedium, could induce the maximum callus wet-weight of 1,69 g and the fastest callus initiation time of 4,8 day.